Trade Liberalization and Welfare Inequality: a Demand-Based Approach - Alexander Tarasov (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
There is strong evidence that different income groups consume different bundles of goods. This evidence suggests that trade liberalization can affect welfare inequality within a country via changes in the relative prices of goods consumed by different income groups (the price effect). In this paper, I develop a framework that enables us to explore the role of the price effect in determining welfare inequality. There are two core elements in the model. First, I assume that heterogenous in income consumers share identical but nonhomothetic preferences. Secondly, I consider a monopolistic competition environment that leads to variable markups affected by trade and trade costs. I nd that trade liberalization does affect the prices of different goods differently and, as a result, can benefit some income classes more than others. In particular, I show that the relative welfare of the rich with respect to that of the poor has a hump shape as a function of trade costs.
urn:nbn:de:bvb:19-epub-11492-5
Keywords: F12; 330; nonhomothetic preferences; income distribution; monopolistic competition; Handelsliberalisierung; Produktdifferenzierung; Monopolistischer Wettbewerb; Außenhandelsgewinn; Soziale Ungleichheit; Konsumentenverhalten; Einkommensverteilung; Präferenztheorie; Wohlfahrtsanalyse; Theorie